2021
DOI: 10.1186/s13098-021-00741-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of anti-oxidative capacity of HDL with subclinical atherosclerosis in subjects with and without non-alcoholic fatty liver disease

Abstract: Background Non-alcoholic fatty liver disease (NAFLD) patients are at a substantial risk for developing cardiovascular disease (CVD). High-density lipoprotein (HDL) is well known to have protective effects against the development of atherosclerotic CVD. One of the major antiatherogenic effects of HDL is its anti-oxidative function. Objectives This study investigated the association of anti-oxidative capacity of HDL with subclinical atherosclerosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…20 Karami et al found that HDL anti-oxidative functionality might contribute to NAFLD pathogenesis. 21 A new indicator has recently been proposed by Ko et al, namely triglyceride glucose-body mass index (TYG-BMI). Noticeably, TYG-BMI was universally regarded as a more effective predictor of IR (Insulin resistance).…”
Section: Introductionmentioning
confidence: 99%
“…20 Karami et al found that HDL anti-oxidative functionality might contribute to NAFLD pathogenesis. 21 A new indicator has recently been proposed by Ko et al, namely triglyceride glucose-body mass index (TYG-BMI). Noticeably, TYG-BMI was universally regarded as a more effective predictor of IR (Insulin resistance).…”
Section: Introductionmentioning
confidence: 99%
“…Some regard NAFLD as a hepatic manifestation of METS ( 16 ). Additionally, in previous reports, reduced HDL-c efflux capability and anti-oxidative activity may contribute to the pathophysiology of NAFLD ( 17 ). Given the correlation between GGT and HDL-c and NAFLD, it is vital to investigate the association between the GGT/HDL-c ratio and NAFLD.…”
Section: Introductionmentioning
confidence: 82%
“…In addition, oxidative stress plays a fundamental role in the initiation and progression of NAFLD ( 50 ). Thus, HDL-c anti-oxidative activity might contribute to NAFLD pathogenesis ( 17 ). With high GGT/HDL-c ratios, high GGT with low HDL-c levels may be related to NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical setting, it is widely accepted that antioxidant effects are mostly related to age-related diseases [ 65 ], such as cardiovascular disease [ 66 , 67 ], non-alcoholic fatty liver disease [ 67 ], vascular dementia [ 68 ], Graves’ ophthalmopathy [ 69 ], cancer [ 70 , 71 ], diabetes [ 72 ], etc. ROS, including hydrogen peroxide (H 2 O 2 ), hydroxyl radical (•OH), singlet oxygen (1O 2 ), superoxide (O 2 2− ), etc., is a group of unstable molecules produced by various cells in the human body.…”
Section: Research Progress On Pharmacological Activitymentioning
confidence: 99%